2019
DOI: 10.1002/jbmr.3805
|View full text |Cite
|
Sign up to set email alerts
|

TNFRSF11A-Associated Dysosteosclerosis: A Report of the Second Case and Characterization of the Phenotypic Spectrum

Abstract: Dysosteosclerosis (DOS) is a distinct form of sclerosing bone disease characterized by irregular osteosclerosis and platyspondyly. DOS is genetically heterogeneous; however, only five cases with SLC29A3 mutations and a single case with a splice-site mutation of TNFRSF11A have been reported, and TNFRSF11A is also a causal gene for osteopetrosis, autosomal recessive 7 (OP-AR7). Thus, the causal genes of DOS and their genotype-phenotype associations remain unclear. In this study, we examined a Japanese patient wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…In contrast, the radiolucency in the enlarged lower metaphyseal parts was diffuse in the older cases (Case 1 and 2) (Guo et al, 2018;Xue et al, 2019). Moreover, although platyspondyly were found in all cases, concaved vertebrae at posterior thirds were present only in the older cases (Table 1) (Guo et al, 2018;Xue et al, 2019). In this study, our patient at age 19 months showed similarities to the previous young cases in both spinal and submetaphyseal changes (Figures 1C,E; Table 1).…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…In contrast, the radiolucency in the enlarged lower metaphyseal parts was diffuse in the older cases (Case 1 and 2) (Guo et al, 2018;Xue et al, 2019). Moreover, although platyspondyly were found in all cases, concaved vertebrae at posterior thirds were present only in the older cases (Table 1) (Guo et al, 2018;Xue et al, 2019). In this study, our patient at age 19 months showed similarities to the previous young cases in both spinal and submetaphyseal changes (Figures 1C,E; Table 1).…”
Section: Resultssupporting
confidence: 67%
“…Generally, the young cases (Case 3 and 4) had a clear radiolucent band in the submetaphyseal region of tubular bones, which was widely splayed and sclerotic (Xue et al, 2020;Xue et al, 2021a). In contrast, the radiolucency in the enlarged lower metaphyseal parts was diffuse in the older cases (Case 1 and 2) (Guo et al, 2018;Xue et al, 2019). Moreover, although platyspondyly were found in all cases, concaved vertebrae at posterior thirds were present only in the older cases (Table 1) (Guo et al, 2018;Xue et al, 2019).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…DOS is mainly characterized by diffuse osteosclerosis, platyspondyly, and radiolucency of widened submetaphyseal portions of the tubular bones [20]. SLC29A3 and TNFRSF11A have been reported as the causal genes for DOS [21][22][23][24][25][26]. Pyle disease is caused by bi-allelic SFRP4 mutations and characterized by thin cortices, bone fragility and expanded trabecular metapyhyses [27].…”
Section: Banddosmentioning
confidence: 99%